Spontaneous Heterotopic Pregnancy, Simultaneous Ovarian, and Intrauterine: A Case Report. (10th September 2012) - Basile, Francesca; Di Cesare, Cristina; Quagliozzi, Lorena; Donati, Laura; Bracaglia, Marina; Caruso, Alessandro; Paradisi, Giancarlo
Abstract : Spontaneous heterotopic pregnancy is a rare clinical condition in which intrauterine and extrauterine pregnancies occur at the same time. The occurrence of an ovarian heterotopic pregnancy is a singular event as it comprises only 2.3% of all heterotopic pregnancies, extremely rare among women who conceive naturally. A case of a 28-year old patient was treated for spontaneously conceived heterotopic pregnancy. The patient was admitted to our center with lower abdominal pain and amenorrhoea. A transvaginal ultrasound scan showed an ovarian and an intrauterine heterotopic pregnancy. This was managed laparoscopically. Considering spontaneous pregnancies, every physician treating women of reproductive age should be aware of the possibility of heterotopic pregnancy. It can occur in the absence of any predisposing risk factors; only with an early diagnosis and treatment the intrauterine pregnancies will reach viability with a great chance of a favorable obstetric outcome.